2013
DOI: 10.2134/jeq2013.04.0113
|View full text |Cite
|
Sign up to set email alerts
|

Hardwood Tree Growth after Eight Years on Brown and Gray Mine Soils in West Virginia

Abstract: Surface coal mining in Appalachia disturbs hundreds of hectares of land every year with the removal of valuable and ecologically diverse eastern deciduous forests. After the passage of the Surface Mining Control and Reclamation Act in 1977, coal mine operators began planting a variety of grasses and legumes as a fast and economical way to reestablish a permanent vegetative cover to meet erosion and site stabilization requirements. However, soil compaction and competitive forage species have arrested the recolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 33 publications
(58 reference statements)
6
30
0
Order By: Relevance
“…The West Virginia site was constructed using a mixture of brown and gray spoils, while the plots in our study were constructed using predominately brown spoils [14]. A series of recent studies have indicated that brown spoils tend to provide a better growing medium for native hardwoods than gray, less weathered spoils [8,10,36,37]. Soil pH in West Virginia (5.8) was within the preferred range of the American chestnut (5.5-6.5 [38]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The West Virginia site was constructed using a mixture of brown and gray spoils, while the plots in our study were constructed using predominately brown spoils [14]. A series of recent studies have indicated that brown spoils tend to provide a better growing medium for native hardwoods than gray, less weathered spoils [8,10,36,37]. Soil pH in West Virginia (5.8) was within the preferred range of the American chestnut (5.5-6.5 [38]).…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines, in brief, are: (1) select the best available growth medium; (2) minimize compaction; (3) minimize vegetative competition; (4) plant both early and late-succession trees; and (5) use proper planting techniques [7]. A number of studies have confirmed that sites planted according to FRA are characterized by high tree survival and growth [8][9][10]. Because a majority of the land affected by surface mining lies in the center of the historical American chestnut range, Appalachian mined land has been targeted for blight-resistant chestnut restoration efforts [11].…”
Section: Introductionmentioning
confidence: 99%
“…Sorenson et al (2011) found that coniferous stands were linked with fungal presence, whereas aspen stands had a stronger bacterial component. The type of soil replacement or substrate amendment can be clearly linked with differences in both vegetation (Angel et al 2008;Miller et al 2012;Wilson-Kokes et al 2013a) and microbial biomass and composition (Machulla et al 2005;Palumbo et al 2004;Chodak and Niklinska 2010). Vegetation affects soil microbial communities by the quantity and quality of litter while microbes, in turn, influence re-vegetation success (Jasper 2007).…”
Section: Soil Microbial Processesmentioning
confidence: 99%
“…Overall, longer-term survival and growth of trees is better in weathered brown materials than in unweathered gray sandstone, siltstone, shale (Angel et al 2008;Emerson et al 2009;Wilson-Kokes et al 2013a) (Table 1). This has been attributed to a slightly acid pH, low soluble salts, good drainage and aeration, and better water retention compared to most unweathered rock materials.…”
Section: Creating the Conditions For Vegetation Establishmentmentioning
confidence: 99%
“…Soil phosphorus on S1 and S2 was low because the soil fines fraction was also low (6% and 2% compared to 70% and 38% on S3 and S4) [38], causing less phosphorus to be available to plants [39]. In addition, decreased of the phosphorus concentrations in both S1 and S2 are probably due to organic matter adsorbing extractable phosphorus or to microbial uptake of available phosphorus for organic matter decomposition.…”
Section: Limiting Factors For Revegetationmentioning
confidence: 99%